Art in the age of Aquarius 1955-1970 - Price, Marla; Rosenblum, Robert; Seitz, William C. (Washington : Smithsonian Institution Washington, 1992)
Agam, Yaacov ; de Andrea, John ; Anuszkiewicz, Richard ; Artschwager, Richard ; Bladen, Ronald ; Bontecou, Lee ; Brancusi, Constantin ; Calder, Alexander ; Caro, Anthony ; Chamberlain, John ; Close, Chuck ; Cornell, Joseph ; D'Arcangelo, Allan ; Davis, Gene ; Demuth, Charles ; Dine, Jim ; Estes, Richard ; Feitelson, Lorser ; Riverhead (New York) ; Frankenthaler, Helen ; Gilbert & George ; Gilliam, Sam ; Goings, Ralph ; Grosvenor, Robert ; Haacke, Hans ; Hanson, Duane ; Heizer, Michael ; Hopper, Edward ; Indiana, Robert ; Johns, Jasper ; Judd, Donald ; Kaprow, Allan ; Kelly, Ellsworth ; Kienholz, Edward ; Klein, Yves ; de Kooning, Willem ; Lichtenstein, Roy ; Louis, Morris ; de Maria, Walter ; Marisol ; Matisse, Henri ; McLean, Richard ; Morris, Robert ; Newman, Barnett ; Oldenburg, Claes ; Olitski, Jules ; Oppenheim, Dennis ; Pollock, Jackson ; Poons, Larry ; Rauschenberg, Robert ; Reinhardt, Ad ; Riley, Bridget ; Rivers, Larry ; Rosenquist, James ; Rothko, Mark ; Samaras, Lucas ; Schwitters, Kurt ; Segal, George ; Shemi, Yeleni ; Smith, David ; Smith, Tony ; Smithson, Robert ; Snelson, Kenneth ; Soulages, Pierre ; Spoerri, Daniel ; Stankiewicz, Richard ; Stella, Frank ; Still, Clyfford ; Suvero, Mark di ; tadasky ; Tinguely, Jean ; Truitt, Anne ; Warhol, Andy ; Wesselmann, Tom ; Whitman, Robert
Chronologie p. 205-239
Engels
boek